KAJIAN ETNOKOREOLOGI TARI YUDHARINI KARYA IYUS RUSLIANA DI SMKN 10 BANDUNG - Fitri Febrianty, - (2018)
This research entitled "The Study of Ethnocoreology of Yudharini Dance Created by IyusRusliana in SMKN 10 Bandung". The research was conducted at ISBI and SMKN 10 Bandung with Mr. IyusRusliana as the interviewee. Yudharini Dance is one of the dances that belongs to puppet dance genre. This dance includes a type of princess war dance with character of princess ladak. Yudharini Dance is originated from two words that are Yuda and Rini. Yuda means war and Rini means daughter in which when being united Yudharini denotes princess war. Yudharini Dance is a warrior of Srikandi. Yudharini becomes a country shield in the kingdom of Amarta. The purpose of this research was to obtain a comprehensive picture of Yudharini Dance which was obtained through the analysis of background creation, choreography structure, make up and dress, and Yudharini character from educational perspective. This research employed descriptive analysis method which was studied through the study of ethnocoreology. The analysis undertaken in this study focused on the text and context of the dance. The data were collected from observation, interview, documentation and literature study by using triangulation data analysis. Yudarini Dance is one of the puppet dances coming from Garut that has a variety of war motion, patokan, campuh and ngalaga. Based on the study of ethnocoreology, it can be found out that motion analysis in the laban or notation research system is categorized into locomotion, pure movement, gesture.Rias and busana refer to the make-up and clothing used in the puppet show. The dance accompaniment or music used is larassalendroand and on the dance, there are nyandra or kakawen. Yudarini Dance also provides values of character education.;--Penelitianiniberjudul "Kajian Etnokoreologi Tari Yudharini Karya Iyus Rusliana di SMKN 10 Bandung". Penelitian dilaksanakan di ISBI dan SMKN 10 Bandung dengan Narasumber bapak Iyus Rusliana. Tari Yudharini merupakan salah satutari yang termasuk genre tari Wayang. Tari ini termasukjenis tari perang putri yang berkarakter putriladak. Tari Yudhar ini diambil dari dua kata yaitu Yuda dan Rini, yuda yang diartikan perang dan rini yang artinya putrid bila disatukan Yudharini adalah perang putri. Tari Yudharini ini adalah Prajurit dari Srikandi. Yudharini menjadi tameng nagara di kerajaan Amarta. Tujuan penelitian ini adalah untuk mendapatkan gambaran secara menyeluruh tari Yudharini. yang didapatkan melalui analisis tentang latar belakang terciptanya, struktur koreografi, tata rias busana, serta karakter yudharini dari prespektif Pendidikan. Metode yang digunakan dalam penelitian adalah metode Deskriptif analisis yang dikaji melalui kajian Etnokoreologi. Analisis yang dilakukan pada kajian ini terfokus pada bagian teks dan kontekstarinya. Teknik pengumpulan data yang dipergunakan melalui observasi, wawancara dokumentasi dan studi pustaka, dengan analisis data menggunakan triangulasi. Tari Yudharini adalah salah satu tari wayang yang berasal dari Garut memiliki ragam gerak perang patokan, campuh dan ngalaga. Berdasarkan kajian etnokoreologi maka bias diketahui bahwa analisi gerak pada penelitian system labanataunotasi yang dikategorikanlocomotion (gerakber pindah tempat), pure movement (gerak murni), gesture (gerak maknawi). Rias busana tari ini mengacu kepada rias dan busana pada pertunjukan wayang golek. Iringan tari atau musiknya menggunakan larassalendro dan pada tarinya ada nyandr aatau kakawen. Pada tari yudharini ada nilai-nilai Pendidikan karakter didalamnya.